Characterization of a nuclear protein that binds to three elements within the silencer region of a bean chalcone synthase gene promoter. - Harrison, M J (1991)
The chalcone synthase (EC 2.3.1.74) gene promoter from the bean Phaseolus vulgaris L. contains a silencer element between positions -140 and -326 fro the transcription start site that is functional in electroporated soybean protoplasts. This element contains three binding sites for a bean nuclear factor (SBF-1) with DNA sequence recognition properties that are very similar to those of nuclear factor GT-1. By using a synthetic tetramer of one of the binding sites as probe, we have purified sequence-specific SBF-1 activity approximately 1750-fold from suspension-cell nuclei, by using a combination of ammonium sulfate precipitation, gel filtration, heparin-agarose chromatography, and sequence-specific DNA affinity chromatography. The factor exhibited an apparent molecular weight of 160,000-200,000 on the basis of gel filtration. A subunit molecular weight of approximately 95,000 was determined from SDS/polyacrylamide gel electrophoretic analysis of purified fractions, followed by Southwestern blot analysis (a protein blot probed with oligonucleotide probes), and from UV-cross-linking experiments. The factor lost DNA-binding activity on treatment with alkaline phosphatase. We discuss the properties of SBF-1 in relation to the functionality of GT-1 binding sequences in plant genes.